Predictors of Chinese secondary school students behavioral intention to use an online homework system in Huicheng, China - Liu, Chen (2024)
As an active response to the popularity of technological applications in the current educational era, online homework systems have been applied to assist students learning worldwide. However, informed studies have identified that Chinese secondary school students are hesitant and unwilling to accept them for learning. Hence, it is imperative to determine the factors that predict behavioral intention to use an online homework system among students due to the great benefits this technology offers to them for learning. This study aimed to explore the extent of behavioral intention to use an online homework system among the secondary school students in Huicheng District, Huizhou, Guangdong, China. It also determined the predictive function of eight proposed independent variables, namely performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, interest, attitude, and technological self-efficacy, on the dependent variable behavioral intention to use an online homework system among the students. The data were collected from the eighth graders of four selected public schools in Huicheng District (N = 1,466). A stratified random sample of 339 students was selected. Based on the data analysis from the distribution of questionnaires, the reliability testing produced an acceptable internal consistency where the Cronbach alpha value was higher than 0.70 using the SPSS 26. The descriptive statistics were then presented. The associations between the independent and dependent variables were conducted by the Pearson’s Product Moment coefficient. The proportion of the variances in behavioral intention explained by the proposed variables was identified via multiple regressions. Additionally, an indepth interview with 10 purposively selected students were followed up by the quantitative stage to explore some underestimated predictors of behavioral intention to use an online homework system among the students. The findings in this study indicated that the students had a moderate intention to use an online homework system for learning. Besides, their intentions to use the system was predicted by many proposed variables in this study, including attitude, facilitating conditions, interest, social influence, and effort expectancy. Evidently, the students who held positive attitudes towards the system showed greater inclinations to use the system for learning based on the data analyzed (β = 31%). Besides, the students with higher interests in using the system also had the tendency to use it for study (β = 23%). Moreover, the adequate support of facilitating conditions, the sufficient emphasis on social influence, and the low effort expectation to use the system also promised higher possibilities to accept the technology for learning purposes among the students. More than half of the behavioral intention variance (78.5%) of using an online homework system was explained by the selected variables. Based on the findings, the study highlighted sufficient attention should be focused on attitudes, facilitating conditions, interests, social influences, and effort expectancy. These factors were identified to predict the behavioral intentions to use an online homework among the students in the Chinese educational context. Hence, the findings provided the benefits and new insights into the current educational policies and methodologies, as well as some tips for stakeholders to adjust the design of their systems to suit the students’ learning requirements.